Reading comprehension difficulties encountered by senior high school EFL students - Rizka Puji Lestari; Siti Sarah Fitriani; Nira Erdiana (Universitas Syiah Kuala, 2017)
This study aims at finding out reading comprehension difficulties faced by the EFL students and the factors of the difficulties faced by thirty second graders of senior high school Banda Aceh. This research used mix method and the data were collected through test and interview. This research focused on five aspects in reading comprehension namely main idea, detail information, inference, reference, and vocabulary. The data collected were analyzed quantitatively and qualitatively. The quantitative approach was used to obtain the data about the frequency of students’ difficulties in reading comprehension, while the qualitative approach was used to find out the factors why students face the difficulties. Based on the result from the test, the researcher found that the major difficulty students face in reading comprehension text is vocabulary (27%), followed by main idea (23%), inference and reference (18%), and detail information (14%). Moreover, the result from the interview with five students who got the lowest scores in the test and an English teacher who teaches the class indicates that the factors why the students face the difficulties are the absence of extensive reading, inadequate vocabulary, type of text, type of questions, the absence of the use of reading strategy, and the uncertainty of students’ reading levels. The findings suggest the English teacher measures the students’ reading levels properly, clearly teach the reading strategy, and apply an interesting strategy in teaching reading to motivate the students to read in English more.